2021
DOI: 10.1088/1361-6633/ac1e32
|View full text |Cite
|
Sign up to set email alerts
|

Highest resolution chemical imaging based on secondary ion mass spectrometry performed on the helium ion microscope

Abstract: This paper is a review on the combination between Helium Ion Microscopy (HIM) and Secondary Ion Mass Spectrometry (SIMS), which is a recently developed technique that is of particular relevance in the context of the quest for high-resolution high-sensitivity nano-analytical solutions. We start by giving an overview on the HIM-SIMS concept and the underlying fundamental principles of both HIM and SIMS. We then present and discuss instrumental aspects of the HIM and SIMS techniques, highlighting the advantage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 248 publications
0
36
0
Order By: Relevance
“…25,34,35 A most recent review summarizes the applications of HIM−SIMS. 36 On the other hand, as the GFIS has the ability to create the light element He + beam, scanning transmission ion microscopy (STIM) can be explored on the HIM. The typical 30 keV He + beam used in the HIM has a projected range spanning from tens to a few hundreds of nanometers in most materials (SRIM simulations).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,34,35 A most recent review summarizes the applications of HIM−SIMS. 36 On the other hand, as the GFIS has the ability to create the light element He + beam, scanning transmission ion microscopy (STIM) can be explored on the HIM. The typical 30 keV He + beam used in the HIM has a projected range spanning from tens to a few hundreds of nanometers in most materials (SRIM simulations).…”
Section: ■ Introductionmentioning
confidence: 99%
“…In this way, it is possible to perform SIMS analysis of surfaces with excellent detection sensitivity, a high dynamic range (signal variations over several orders of magnitude are detectable), and differentiating the various isotopes . It has been demonstrated that SIMS on the HIM can be performed with sub-20 nm lateral resolution, which gives outstanding results in that respect compared to standalone SIMS tools. , The application fields covered by investigations using SIMS on the HIM range from thin-film studies, battery research, and optoelectronic devices characterization, , to solar cell materials or steel investigations, to geological and biological relevant topics. ,, A most recent review summarizes the applications of HIM–SIMS …”
Section: Introductionmentioning
confidence: 99%
“…While magnetic sector SIMS systems used to be bulky and heavy, modern systems can be compact and considerably lighter thanks to advances in charged particle optics, electromagnet coil concepts, and mechanical assembly design. 19 , 20 …”
mentioning
confidence: 99%
“…We developed compact magnetic sector SIMS systems specifically designed and adapted for the ZEISS ORION NanoFab Helium Ion Microscope (HIM) [1][2][3], Thermo Fisher DualBeam platforms [4] and the ZeroK FIB:ZERO, a FIB platform with a Cesium LoTIS [5]. These instruments are capable of producing elemental SIMS maps with sub-15 nm lateral resolution, while maintaining the performance of the FIB platform in terms of secondary electron (SE) imaging and nanomachining.…”
mentioning
confidence: 99%